IMPLEMENTASI BALANCE SCORE CARD PERSPEKTIF PENJAMINAN MUTU PENDIDIKAN ISLAM - Nisrina Nabilah; Munirul Abidin (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2022)
Abstract The orientation of this article is to investigate and examine more deeply the meaning of the balance score card, aspects of the balance score card and its implementation in the perspective of quality assurance of Islamic education. In this paper, the author tries to analyze more deeply and systematically in implementing new management strategies that can encourage quality improvement in institutions by using a balanced score card approach based on Islamic principles. The type of research in this article uses a library research approach in which data collection techniques are obtained from various primary references and secondary data which are then reduced and keyed. Research results: (1). Application of Balance Score Card in Islamic Education Quality that is balanced both financially (profit) and non-financially (non-profit), (2). Standardization of Performance Measures from the Perspective of the Balance Score Card (in terms of finance, customers, internal business processes and learning and growth). With a comprehensive performance measurement that does not only measure financial but combines financial and non-financial measures, educational institutions can carry out better organizational performance. Keywords: Balance Score Card; Quality Assurance; Islamic Education. Abstrak Orientasi artikel ini untuk menyelisik dan menelaah lebih dalam makna balance score card, aspek balance score card dan implementasinya dalam perspektif penjaminan mutu Pendidikan Islam. Dalam tulisan ini penulis mencoba menganalisis lebih dalam serta sistematis dalam menerapkan strategi manajemen baru yang dapat mendorong peningkatan mutu di lembaga dengan menggunakan pendekatan balance score card disandari dengan prinsip-prinsip Islam. Jenis penelitian dalam artikel ini menggunakan pendekatan Library research yang mana teknik pengumpumlan data diperoleh dari pelbagai referensi  primer dan sekunder yang kemudian data direduksi dan disimpulkan. Hasil penelitian: (1). Penerapan Balance Score Card dalam Mutu Pendidikan Islam yang secara seimbang baik secara financial (profit) dan non-financial (non-profit), (2). Standarisasi Ukuran Keberhasilan Kinerja Perspektif Balance Score Card (dalam aspek keuangan, pelanggan, proses bisnis internal dan pembelajaran dan pertumbuhan). Dengan pengukuran kinerja yang komprehensif tidak hanya mengukur keuangan tetapi menggabungkan ukuran keuangan dan non-keuangan, lembaga pendidikan dapat menjalankan kinerja organisasi yang lebih baik. Kata Kunci: Balance Score Card; Penjaminan Mutu; Pendidikan Islam.